CABARAN ABAD 21 DAN KEPERLUAN AMALAN KEROHANIAN OLEH WARGA EMAS - Muhammad Khairi Mahyuddin; Roslee Ahmad; Atifah Mamat; Awatif Abdul Rahman (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
Spirituality is an important aspect of internal humanity. It is also related to the issue of the heart, feeling and nature want to return to God. The spiritual aspect was initially given attention by the gold residents when their age was stepping on aging and physical desolation. The objective of this study is to find out about the needs of spiritual practice by the citizens of gold and its impression on peace of mind and the stability of monotheism in God. The methodology of this study is intellectual and conceptual. The terms of spiritual needs and rituals are elaborated through the Koran, Hadith and the books of Islam. The results can be found that spiritual practice is needed by gold residents. When the tranquility and stability of monotheism is achieved through knowledge, mujahadah and sharia practices and the Sunnah of the Prophet Saw.